EDUKASI “ADVENTURE OF UNITY-CHAN” UNTUK PEMBELAJARAN FISIKA KELAS 10 SMK - Vadlya Maarif; Hidayat Muhammad Nur; Ragil Wijianto; Kaliman Kaliman (Evolusi : Jurnal Sains dan Manajemen, 2020)
As the development of technology can cause various positive and negative influences, one of the negative effects is that many people are addicted to gadgets and games. Playing games is fine, but usually the stigma in society is children who play games too often, so they tend to forget and ignore their education and prioritize games where it is feared that it will affect their academic performance. At present many developers apply the educational element to the games they make, in contrast to games that have recently become popular, the educational game can be an additional lesson for students in addition to the material obtained from school. Because using educational game media is more attractive to students to learn, the author intends to create an Educational Game "Adventure of Unity-Chan" for Physics Learning  Class 10 of Vocational School, which is expected to be used as an alternative learning media so that classroom teaching and learning activities do not experience saturation.